Photoconductive antennas based on epitaxial films In0.5Ga0.5As on GaAs (1 1 1)A and (1 0 0)A substrates with a metamorphic buffer. (1st June 2018) - Kuznetsov, K A; Galiev, G B; Kitaeva, G Kh; Kornienko, V V; Klimov, E A; Klochkov, A N; Leontyev, A A; Pushkarev, S S; Maltsev, P P
Abstract: The terahertz (THz) wave generation by the spiral photoconductive antennas fabricated on the low-temperature and high-temperature grown undoped and Si-doped In0.5 Ga0.5 As films is studied by the terahertz time-domain spectroscopy method. The In0.5 Ga0.5 As layers were grown by molecular beam epitaxy on GaAs substrates with (1 0 0) and (1 1 1)A crystallographic orientations utilizing step-graded In x Ga1− x As metamorphic buffer. The antennas are excited by radiation of Er 3+ -fiber laser at 1.56 μ m wavelength in two regimes: with pulse durations of 2.5 ps or 100 fs. It is found that the THz wave generation is 3–4 times more effective in the case of InGaAs-based antennas on (1 1 1)A GaAs substrates as compared to the (1 0 0) substrates. Power-voltage characteristic of the LT-InGaAs antenna up to and beyond threshold breakdown voltage are reported.